Astilbin attenuates neonatal postnatal immune activation-induced long-lasting cognitive impairment in adult mice. (March 2023) - Zhao, Tiantian; Wang, Dongshuang; Wu, Dong; Du, Jingyi; Zhao, Man; Peng, Fan; Zhang, Meihua; Zhou, Wenjuan; Hao, Aijun
Graphical abstract: Highlights: ASB improves postnatal immune activation (PIA)-induced cognitive impairment. ASB exerts neuroprotection by inhibiting neuronal apoptosis and promoting neurogenesis. ASB regulates BCL2 expression via H3K27me3 in neurons. Abstract: Postnatal immune activation (PIA) often induces neuroinflammation and disrupts neural functions, ultimately causing cognitive impairment. Among them, neuronal dysfunction is one of the key causes of many neurological diseases. It is particularly important to develop effective neuroprotectants to prevent inflammatory brain diseases. Recently, the protective effect of astilbin (ASB) on nervous system diseases has attracted much attention. However, whether ASB can resolve neuronal dysfunction and cognitive decline triggered by PIA remains unclear. In this study, we used the lipopolysaccharide (LPS)-induced PIA model and found that ASB improved PIA-induced cognitive impairment and neuronal dysfunction in adult mice. Moreover, ASB inhibited PIA-induced neurogenesis deficits and synaptic damage. Finally, we found that ASB treatment inhibited the levels of EZH2/H3K27me3 and decreased the enrichment level of H3K27me3 at the promoter of BCL2 and BDNF. Together, our results demonstrated that ASB may protect against PIA-induced cognitive impairment through EZH2-mediated histone methylation. This study established the role of ASB and epigenetic factor EZH2 regulatory network on the PIA model, which provided new clues and theoretical guidance for the clinical treatment of PIA-induced cognitive impairment.